2020
DOI: 10.1159/000512170
|View full text |Cite
|
Sign up to set email alerts
|

Limited Impact of Anti-PD-1/PD-L1 Monotherapy for Hepatocellular Carcinoma

Abstract: Two ICIs are approved by the United States Food and Drug Administration (FDA) for HCC: nivolumab as second-line therapy following progression on sorafenib (based on the results of the phase I/II CheckMate 040 study) [3], and pembrolizumab as second-line therapy (based on the phase I/II KEYNOTE-224 study) [4]. However, the confirmatory phase III CheckMate 459 study [5] (nivolumab vs. sorafenib) and the second-line phase III KEYNOTE-240 study [6] (pembrolizumab vs. placebo) both failed; therefore, approval of ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 27 publications
0
21
0
Order By: Relevance
“…Afterwards, the combination therapy revealed significantly better therapeutic outcomes and safety than sorafenib. In real-world clinical practice, the combination therapy can be used not only for the MTA-naïve cases but also the MTA-experienced cases as second- or third-line treatment [ 11 ]. Therefore, clarification is needed whether atezolizumab plus bevacizumab can be administered even for the MTA-experienced cases with safety.…”
Section: Introductionmentioning
confidence: 99%
“…Afterwards, the combination therapy revealed significantly better therapeutic outcomes and safety than sorafenib. In real-world clinical practice, the combination therapy can be used not only for the MTA-naïve cases but also the MTA-experienced cases as second- or third-line treatment [ 11 ]. Therefore, clarification is needed whether atezolizumab plus bevacizumab can be administered even for the MTA-experienced cases with safety.…”
Section: Introductionmentioning
confidence: 99%
“…This was precisely veri ed by the recent report by Chen et al, in which patients had increased PD-1 inhibitor treatment on the basis of TACE with improved oncological outcomes [14]. However, the role of PD-1 inhibitors for patients is also limited [34], and once a patient presents refractory to both PD-1 inhibitors and TACE, what treatment should be followed up, which is a question worth exploring and urgently resolving.…”
Section: Discussionmentioning
confidence: 97%
“…In 2020, Finn et al reported results from the phase Ib KEYNOTE 524 trial, that evaluated the (27). It is evident from the results of the above trials that immunotherapy in combination with other targeted therapies exhibit a superior antitumor activity compared to single-agent immunotherapy (28). Nonetheless, current evidence for combination treatment strategies arises from early-stage trials with small sample sizes.…”
Section: Review Articlementioning
confidence: 99%